Pengelolaan Barang Milik Negara Bidang Hulu Minyak dan Gas Bumi - Sumartono Sumartono; Syarif Budiman; Ahmad Ahmad; Fakhri Aldifha Kurnia; Irwansyah Irwansyah; Isam Tuanaya (Journal on Education, 2023)
Indonesia has enormous natural wealth that must be managed properly and based on the Constitution of the Republic of Indonesia Year 1945 controlled by the state and used to the greatest extent for the prosperity of the people. The management of natural wealth in the oil and gas sector is carried out by business entities, both state-owned enterprises, regional-owned enterprises, private businesses, both foreign private and national self-reliance. To produce oil and gas requires a very large investment both for research, exploration, and exploitation as well as equipment. The equipment used by the Cooperation Contract Contractor (KKKS) for upstream oil and gas activities in accordance with Government Regulation no. 35 of 2004 is State Wealth/State Property (BMN). The determination of BMN is stated in the cooperation contract signed between the government and KKKS. Thus, the equipment is a BMN based on a contractual agreement in accordance with Government Regulation number 27 of 2014 as updated by Government Regulation no 28 of 2020, and reported in the Central Government Financial Statements (LKPP).